Predictors of linear sprint performance in professional football players - Barrera, J.; Figueiredo, A. J.; Duarte, J.; Field, A.; Sarmento, H. (Biology of Sport, 2023)
The purpose of this study was to analyze the relationship between sprint performance (time), and strength and power capabilities in football players. A total of 33 professional Portuguese football players performed isokinetic strength assessments, countermovement jumps (CMJ), squat jumps (SJ), and 10, 20 and 30 m sprints. Pearson`s correlation (r) was used to determine the relationships between variables. Concentric knee extensor torque at 180° · s-1 was largely-to-very largely correlated with 10 m (r = -0.726), 20 m (-0.657) and 30 m sprints (r = -0.823). Moderate inverse correlation were observed between CMJ (r = -0.425 andr = -0.405) and SJ height (r = -0.417 andr = -0.430), and 20 m and 30 m sprint performance, respectively. Multiple linear regression combining KEcon 180° · s-1 and KFcon 180° · s-1 demonstrated that the model was significant for predicting 10 m sprint time (F (2, 8) = 5.886; R 2 = 0.595). The model combining SJ, CMJ and KEcon 180° · s-1 was also significant for predicting 20 and 30 m sprint times (F (3, 7) = 2.475; R 2 = 0.515 and F (3, 7) = 5.282; R 2 = 0.562; respectively). In conclusion, peak torque at higher velocities and vertical jump performance correlates significantly with linear sprint performance (time). For practitioners seeking to improve linear sprint performance in football players, evaluation of high speed strength and vertical jump indices should be undertaken.